Process analysis and improvement of a Claus unit of an existing gas plant - Gharsalla, Khaled R. M. (Cranfield University, 2016)
This research is a part of Master degree research programme at Cranfield University to study Claus process and perform process analysis on an existing Sulphur recovery unit in a gas plant. The Mellitah Plant, in Western Libya, is a gas plant designed to treat raw gas and condensate from offshore gas fields in several processing units where the sour gas (H2S, CO2, COS, SC2) is removed to meet the international emission standard, in order to control the emission and pollution from the flue gas. The acid gases are treated in Claus unit where H2S is converted to sulphur in multi-reaction steps. These reactions start in a combustion reaction zone, thermal reactor, to produce a suitable mixture of H2S to SO2. The mixture reacts in Claus catalytic reactors to produce sulphur vapour. The sulphur vapour is condensed in multi-condensing steps after each catalytic reactor. The ultimate aim of this research is to carry out the process analysis for Claus unit in order to recover the waste energy to increase the plant productivity, minimise the use of the plant utilities, and decrease the environmental pollution. A process model of the plant was developed and validated in Aspen HYSYS. The process was then analysed, the analysis has resulted in a significant increase in Claus unit overall conversion ratio which has increased from 61% to 97.63% H2S base. Consequently, Claus unit productivity has increased by approximately 1.72 times. In addition, a higher amount of energy is recovered in a form of heat by heating the boiler feed water to produce both high pressure steam in the waste heat boiler and low pressure steam in 1st and 2nd sulphur condensers. Both high pressure and low pressure steam total production are increased by 1.5 times. All this has been achieved at high conversion ratio number of 2 in tail gas which represents optimum O2/H2S ratio in the thermal reactor feed and the high conversion number can be kept in between 1.5 to 3 during plant normal operation.
Keywords: Acid gas composition; O2 concentration; ratio O2/H2S; Claus Unit; H2S/SO2 ratio in tail gas; thermal reactor; catalytic reactor